ENT SURGEONS AS MASTER TRAINERS OF CRICOTHYROIDOTOMY WILL SAVE PRECIOUS LIVES IN EMERGENCIES - Shabbir Bukhari, Syed Muhammad Asad; Aslam, Sohail; Riaz, Naeem; Abbas, Asim; Raza, Maqbool; Fareed, Ghulam (Pakistan Armed Forces Medical Journal, 2021)
Objective: To train young doctors and paramedical staff on needle cricothyroidotomy and surgical cricothyroidotomy and provision of kits in trauma centers, main operation theatres and medical reception centers of the hospitals.Study Design: Quasi experimental study.Place and Duration of Study: Combined Military Hospital Peshawar and Pakistan Naval Ship Shifa, Karachi Pakistan, from Nov 2017 to Oct 2020.Methodology: Doctors and paramedical staff were selected on volunteer basis. Small groups were trained in 2-3hours. The participants were shown two videos of two procedures in Urdu language first and then were trained on mannequin.Results: A total of 345 participants including 205 males and 140 females were trained with mean age was 28.2667 ± 6.24 (SD) years. Out of 61 residents, 54 medical officers, 143 house officers, 35 nurses and 52 paramedical staff were participants.Conclusion: ENT surgeons must arrange mannequins and conduct training sessions of small groups after every 1 to 2 months.